PTH-019 'missed' oesophago- gastric cancers on gastroscopy: are we really missing them all?. (8th June 2018) - Chandrapalan, Subashini; Green, Jessica; Perez, Francisco; Mukhtar, Ahmed; Kejariwal, Deepak
Abstract : Introduction: Oesophago-Gastric (OG) cancer usually present late with consequent poor prognosis. The failure to detect early stage OG cancer at endoscopy may contribute to poor prognosis. A recent meta-analysis reported miss rates of 11.3% for OG cancers at endoscopy up to 3 years prior to diagnosis (1). We looked at our data in the Trust to quantify how often opportunities to diagnose cancer at an earlier stage are missed. Method: A retrospective review was carried out, on the medical records of newly diagnosed gastro-oesophageal cancer patients at County Durham and Darlington NHS Trust between the period 01/08/2014 – 31/07/2017. The data was extracted on patients who had standard light gastroscopy within a period of 3 years prior to the diagnosis. Endoscopic images were reviewed by a panel of 3 consultant gastroenterologists. Results: A total of 181 patients were diagnosed as having gastro-oesophageal cancers during the study period, of whom 12 had gastroscopy within three years. Amongst them, 3 had gastroscopy within one year prior to the diagnosis. The index endoscopy was performed by consultant gastroenterologist in 6 patients, nurse endoscopist in 4 and others in 2 patients. The overall incidence of cancers in patients who had gastroscopy within 3 years and 1 year were 6.6% and 1.6% respectively. Amongst those, 8 were oesophageal, 3 were gastric and 1 of them was junctional cancer. Endoscopic photo documentation was fully retrievable for 6 patients who had endoscopy within 3 years and the review confirmed normal looking mucosa at the anatomical area concerned. (50%). Conclusion: Our study shows, incidence of the oesophageal cancer was high in comparison to gastric or junctional tumours for those who had gastroscopy within 3 years prior to the diagnosis. The normal endoscopic photo documentation in 50% of the patients, suggests interval cancers rather than 'missed' cancers. This raises suspicion on whether we are increasingly dealing with rapidly progressing tumours as suggested by emerging evidence that many cancers develop rapidly by punctuated and catastrophic genome evolution (2). Serial photographic documentation of important anatomical landmarks in accordance with latest BSG guidance (3) and further studies on interval cancers are important for future cancer interception.